Aquatic Activities During Pregnancy Prevent Excessive Maternal Weight Gain and Preserve Birth Weight: A Randomized Clinical Trial. Issue 3 (March 2018) - Bacchi, Mariano; Mottola, Michelle F.; Perales, Maria; Refoyo, Ignacio; Barakat, Ruben
Purpose: The aim of the present study was to examine the influence of a supervised and regular program of aquatic activities throughout gestation on maternal weight gain and birth weight. Design: A randomized clinical trial. Setting: Instituto de Obstetricia, Ginecología y Fertilidad Ghisoni (Buenos Aires, Argentina). Participants: One hundred eleven pregnant women were analyzed (31.6 ± 3.8 years). All women had uncomplicated and singleton pregnancies; 49 were allocated to the exercise group (EG) and 62 to the control group (CG). Intervention: The intervention program consisted of 3 weekly sessions of aerobic and resistance aquatic activities from weeks 10 to 12 until weeks 38 to 39 of gestation. Measures: Maternal weight gain, birth weight, and other maternal and fetal outcomes were obtained by hospital records. Analysis: Student unpaired t test and χ 2 test were used; P values ≤.05 indicated statistical significance. Cohen's d was used to determinate the effect size. Results: There was a higher percentage of women with excessive maternal weight gain in the CG (45.2%; n = 28) than in the EG (24.5%; n = 12; odds ratio = 0.39; 95% confidence interval: 0.17-0.89; P = .02). Birth weight and other pregnancy outcomes showed no differences between groups. Conclusion: Three weekly sessions of water activities throughout pregnancy prevents excessive maternal weight gain and preserves birth weight. Trial Registration: Theclinicaltrial.gov identifier: NCT 02602106.